Inhibition by gold of human lymphocyte stimulation. An in vitro study. Issue 3 (June 1977) - Lies, R B; Cardin, C; Paulus, H E
Abstract : Transformation of lymphocytes stimulated by mitogen, purified protein derivative, and in the mixed lymphocyte culture was significantly inhibited by gold sodium thiomate and gold sodium thiosulphate at concentrations of 5 X 10(-4) to 5 X 10(-5) mol/1.